Pandion haliaetus - Bishop, K. David (Zenodo, 2023)
OSPREY Pandion haliaetus # Local name Man Ginin (Sansundi). Range P. h. cristatus Biak, Supiori, Owi, Numfor, Yapen. Status Resident or Palearctic migrant? First noted by Ripley on Supiori in May 1937 (Mayr & Meyer de Schauensee 1939) and collected by Hoogerheide on 8 December 1953 (Junge 1956). Thereafter recorded by most visitors in May‒December. January 1997: singles at Marauw and Sansundi (SvB). During August 2018 and 2019 up to 3‒6 at the tsunami swamp. 13 January 1994: two on Owi (P. Gregory in litt . 2000). Without more information it is impossible to speculate on the origins of these birds. However, P. h. haliaetus has been recorded as a winter migrant on Sulawesi (Coates & Bishop 1997). Breeding 7 July 1982: KDB observed a pair perched atop a tall dead tree above Kuneff, on the south coast of Supiori whose behaviour suggested they may have been looking to nest. Published as part of Bishop, K. David, 2023, The avifauna of Biak Island, Papua, Indonesia with comments on status, conservation, natural history and taxonomy, pp. 3-62 in Bulletin of the British Ornithologists' Club 143 (1) on page 36, DOI:10.25226/bboc.v143i1.2023.a2, http://zenodo.org/record/11642130